Immune checkpoint inhibitors for unresectable malignant pleural mesothelioma - Giulio Metro; Diego Signorelli; Elio G. Pizzutilo; Laura Giannetta; Giulio Cerea; Miriam Garaffa; Alex Friedlaender; Alfredo Addeo; Martina Mandarano; Guido Bellezza; Fausto Roila (Taylor & Francis Group, 2021)
Unresectable malignant pleural mesothelioma (MPM) is an aggressive disease with a 5-year survival rate of approximately 10%. Recent data suggest that MPM is an immunologically active tumor, in which checkpoint inhibition through the blockade of the anti-cytotoxic T lymphocyte antigen-4 (-CTLA-4) or anti-programmed cell death 1 (PD-1) could play a major therapeutic role. Initially, clinical trials evaluated immune checkpoint inhibitors (ICIs) in the salvage setting after platinum-based chemotherapy with mixed results in terms of efficacy. More recently, the combination of the anti-CTLA-4 agent ipilimumab plus the anti-PD-1 agent nivolumab was tested in the front-line setting, and reported a superior survival as compared to platinum/pemetrexed. While other clinical trials ore ongoing in order to investigate ICIs for MPM, it seems now evident that we have entered a new "era" for the treatment of MPM. In the future, a few issues need to be solved with regard to the use of ICIs for MPM. Among them, there is the identification of biomarkers of sensitivity to immunotherapy that may help enrich the patient population who could benefit the most from treatment, while avoiding for some other patients the potential occurrence of immune-related side effects from therapies that are anticipated to be ineffective.